Solving inverse Sturm–Liouville problem with separated boundary conditions by using two different input data. Issue 10 (3rd October 2018) - Neamaty, Abdolali; Akbarpoor, Shahrbanoo; Yilmaz, Emrah
ABSTRACT: In this study, we consider Sturm–Liouville (SL) equation under the separated boundary conditions on a finite interval. We get the approximate solutions of inverse SL problem by using different input data as eigenvalues and nodes (zeros of eigenfunctions), separately, and calculate the computed errors related to the obtained approximate solutions. To calculate the approximate solutions, we use Chebyshev interpolation technique by applying first kind of Chebyshev polynomials. Eventually, the numerical results are presented by providing some examples.